(untitled) (Delta Medical College Journal, 2015)
Background: Evidence shows that high density lipoproteins (HDLs) may exert multiple anti-atherogenic and anti-thrombotic effects that together decrease the risk of cardiovascular morbidity in hyperlipidaemic state. Experimental studies showed that fresh wheatgrass (Triticum aestivum Linn.) juice exerts lipid lowering effect as well as increases HDL-cholesterol level in rats. Objective: The present study was done to observe the effect of wheatgrass juice on serum HDL-cholesterol on experimentally induced dyslipidaemic rats evident by reduced HDL-cholesterol level. Materials and method: This experimental study was carried out in the Department of Pharmacology & Therapeutics, Dhaka Medical College, Dhaka, from July 2009 to June 2010. A total number of 48 healthy adult male Long Evans rats, age ranging from 2-3 months, and weighing from 140-200 grams were used for the present study. Six rats were taken in each group of total 8 groups treated differently with 1 control group. Rats of the first 5 groups were sacrificed at 29th day and their lipid profile was measured. Rests of the rats were sacrificed at 57th day and their lipid profile was measured. Results: Mean HDL-cholesterol of the group of rats treated with 10 mL/kg grass juice and 1% cholesterol diet, with 10 mL/kg grass juice and with 20 mL/kg grass juice were significantly increased (P<0.05, P<0.05, P<0.01 respectively). The mean HDL-cholesterol of the group treated with Atorvastatin for 28 days were also significantly increased (P<0.001). Conclusion: The present experiment showed that HDL-cholesterol level is increased by ingestion of wheat grass juice in experimental animals. Therefore, it provides the initial step for demonstrating cardio-protective effect of wheatgrass juice by increasing HDL-cholesterol level in blood in dyslipidaemic state. DOI: http://dx.doi.org/10.3329/dmcj.v3i1.22235 Delta Med Col J. Jan 2015; 3(1): 18-24